2007
DOI: 10.1002/bdd.539
|View full text |Cite
|
Sign up to set email alerts
|

Effects of morin on the pharmacokinetics of etoposide in rats

Abstract: This study investigated the effects of orally administered morin, an inhibitor of CYP isozyme and P-glycoprotein (P-gp), on the pharmacokinetics of intravenous and orally administered etoposide in rats. It was reported that etoposide is a substrate for P-gp and metabolized mainly via CYP3A4 and to a lesser degree via CYP1A2 and 2E1. Etoposide was administered through intravenous (2 mg/kg) or oral (6 mg/kg) routes to rats with or without orally administered morin (5 or 15 mg/kg), which was administered 30 min b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 30 publications
4
22
0
Order By: Relevance
“…This result is coincident with the previous study, that the presence of kaempferol significantly increased AUC and C max of tamoxifen, a P-gp and CYP3A4 substrate (Piao et al, 2008), and the presence of morin, a flavonoid, significantly increased AUC and C max of etoposide, by inhibited the P-gp and CYP3A4 in rats intestine and/or liver (Li et al, 2007). Ofer et al 2005, reported efflux of talinolol across Caco-2 cells was reduced by kaempferol without replacement of talinolol from its binding to P-gp.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result is coincident with the previous study, that the presence of kaempferol significantly increased AUC and C max of tamoxifen, a P-gp and CYP3A4 substrate (Piao et al, 2008), and the presence of morin, a flavonoid, significantly increased AUC and C max of etoposide, by inhibited the P-gp and CYP3A4 in rats intestine and/or liver (Li et al, 2007). Ofer et al 2005, reported efflux of talinolol across Caco-2 cells was reduced by kaempferol without replacement of talinolol from its binding to P-gp.…”
Section: Discussionsupporting
confidence: 92%
“…The plasma concentrations of etoposide were determined by a HPLC assay and a modification of the method reported by previous study (Li et al, 2007). Briefly, 0.5 µL of 50 ng/mL podophyllotoxin and 1.2 mL of tertbutylmethylether were mixed with 0.2 mL of the plasma sample in a 2.0 mL polypropylene microtube.…”
Section: Hplc Analysismentioning
confidence: 99%
“…The plasma concentrations of etoposide were determined by HPLC assay, as reported by Li et al (15). Briefly, a 50-!.d aliquot of podophyllotoxin (50 ng/ml dissolved in methanol; internal standard) and a 1.2 ml aliquot of tert-butylmethylether were mixed with a 0.2 ml aliquot of plasma sample in a 2.0 rnl polypropylene microtube (Axygen Scientific Co., CA., USA).…”
Section: Hplc Analysismentioning
confidence: 99%
“…However etoposide has shortcomings of low and variable bioavailability after oral dosing [9,10]. Currently different pharmacological approaches are being explored in order to demonstrate any potentially useful improvement in rate and extent of etoposide absorption into the systemic circulation in the clinical setting of oral therapy [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%